Single Subject Research: Alternatif Penelitian Pendidikan Matematika di Masa New Normal - Sri Adi Widodo; K Kustantini; Krida Singgih Kuncoro; Fiki Alghadari (Journal of Instructional Mathematics, 2021)
After confirming the positive case on March 2, 2020, online learning and distance learning is one of the alternatives for learning that is carried out in Indonesia. Apart from the advantages and disadvantages, this learning is an alternative so that learning continues during the COVID-19 pandemic. In connection with this condition, research in the field of education must also adapt to several new phenomena such as limited face-to-face learning, so researchers need to think about research designs that are relevant to the conditions of the COVID-19 pandemic. Single subject research or often referred to as Single Case Experiment Design is one of the alternative research methods that can be carried out during the COVID-19 pandemic, where one of the characteristics of this research is to focus on one subject, so there is no need to use relatively large subjects to conduct experiments.